The effect of 4% sodium cromoglicate cutaneous emulsion compared to vehicle in atopic dermatitis in children – A meta-analysis of total SCORAD scores. (June 2015) - Stevens, Michael T.; Edwards, Alan M.
Abstract An emulsion containing 4% sodium cromoglicate (4% SCG emulsion) has been developed for the treatment of atopic dermatitis in children. We have conducted a meta-analysis of the primary outcome measure (the change in SCORAD score) used in randomized clinical trials (RCTs) with this product. We conducted a search of standard using the keywords, sodium cromoglicate, cromolyn sodium, topical, atopic dermatitis, clinical trial. We identified 19 clinical studies of which 3 used this 4% SCG emulsion formulation, one was a RCT using the change in SCORAD score. We were given access to two further unpublished RCTs, with this measure. The RCTs included 490 subjects (mean age 5.3 years). Each RCT was multicentre of 12 weeks duration, comparing 4% SCG emulsion with the vehicle in which the SCG was dissolved. Using study as the unit and the fixed effect model, the mean difference (95% CI) in the change in SCORAD score was −2.82 (−5.36; −0.29), p = 0.03. Using centre as the unit, and the fixed effect model, the mean difference (95% CI) in the change in SCORAD score was −2.82 (−5.82; −0.46), p = 0.02. These results support the efficacy of this new topical treatment in children with atopic dermatitis.